Direct comparisons of hand and mouth kinematics during grasping, feeding and fork-feeding actions - Quinlan, D. J.; Culham, J. C. (Frontiers in Human Neuroscience, 2015)
While a plethora of studies have examined the kinematics of human reach-to-grasp actions, few have investigated feeding, another ethologically important real-world action. Two seminal studies concluded that the kinematics of the mouth during feeding are comparable to those of the hand during grasping (Castiello, 1997; Churchill et al., 1999); however, feeding was done with a fork or spoon, not with the hand itself. Here we directly compared grasping and feeding kinematics under equivalent conditions. Participants were presented with differently sized cubes of cheese (10-, 20- or 30-mm on each side) and asked to use the hand to grasp them or to use a fork to spear them and then bring them to the mouth to bite. We measured the apertures of the hand during grasping and the teeth during feeding, as well as reaching kinematics of the arm in both tasks. As in many past studies, we found that the hand oversized considerably larger (~11-27 mm) than the food item during grasping and the amount of oversizing scaled with food size. Surprisingly, regardless of whether the hand or fork was used to transport the food, the mouth oversized only slightly larger (~4-11 mm) than the food item during biting and the oversizing did not increase with food size. Total movement times were longer when using the fork compared to the hand, particularly when using the fork to bring food to the mouth. While reach velocity always peaked approximately halfway through the movement, relative to the reach the mouth opened more slowly than the hand, perhaps because less time was required for the smaller oversizing. Taken together, our results show that while many aspects of kinematics share some similarity between grasping and feeding, oversizing may reflect strategies unique to the hand vs. mouth (such as the need to have the digits approach the target surface perpendicularly for grip stability during lifting) and differences in the neural substrates of grasping and feeding.